Bernolák Nándor (1880–1951), a Debreceni M. Kir. Tudományegyetem második rektora - P. Szabó, Béla (Gerundium, 2011)
Nándor Bernolák (1880–1951), the Second Rector of the Hungarian Royal University of Arts and Sciences in Debrecen. As second rector of the Hungarian Royal University of Arts and Sciences, Debrecen, which was launched in 1914, Nándor Bernolák played an important role in shaping the events of the first years. He was a nationally recognized theoretical criminal jurist when he was invited to chair the department of penal law in Debrecen. In addition to an outline of his brief, seven-year, university career, a discussion of his previous professional activities is offered, and the events of his life pertaining both to the early history of the university and to his subsequent political and legal career are highlighted. Professor Bernolák’s reformist initiatives pertaining to criminal law as well as his attempts aimed at the renewal of law training are likewise reviewed. In summary it is stated that Nándor Bernolák excelled both as a criminal jurist and as a university manager. As regards his political career, it turned out to be rather brief and controversial. In view of the fact that he turned his back to his university commitments, we are obliged to consider him as one of those university professors who was lost for Hungarian higher education when they assumed political commitments.